Angiotensin II prevents calcification in vascular smooth muscle cells by enhancing magnesium influx. (13th September 2015) - Herencia, Carmen; Rodríguez‐Ortiz, M Encarnacion; Muñoz‐Castañeda, Juan R.; Martinez‐Moreno, Julio Manuel; Canalejo, Rocío; Montes de Oca, Addy; Díaz‐Tocados, Juan M.; Peralbo‐Santaella, Esther; Marín, Carmen; Canalejo, Antonio; Rodriguez, Mariano; Almaden, Yolanda
Abstract Background Vascular calcification (VC) is highly prevalent in patients with chronic kidney disease (CKD). Low magnesium levels are associated with VC, and recent in vitro studies confirm a protective role of magnesium, which is mediated by its entry into the VSMCs through the Transient Receptor Potential Melastatin 7 (TRPM7) channel. The role of Angiotensin II (Ang II) on VC is still unclear. As Ang II is able to stimulate TRPM7 activity, we hypothesize that it might prevent VC. Thus, the aim of this study was to dissect the direct effect of Ang II on VC. Materials and methods We worked with a model of high phosphate (HP)‐induced calcification in human aortic smooth muscle cells, which resembles the CKD‐related VC. Results Addition of Ang II to cells growing in HP decreased calcification, which was associated with the upregulation of the osteogenic factors BMP2, Runx2/Cbfa1, Osterix and ALP. A reduction of magnesium entry into the HP‐calcifying cells was found. The treatment with Ang II avoided this reduction, which was reversed by the cotreatment with the TRPM7‐inhibitor 2‐APB. The protective effect of Ang II was related to AT1R‐induced ERK1/2 MAPKinase activation. HP‐induced calcification was also associated with the upregulation of the canonical Wnt/beta‐catenin pathway, while its downregulation was related to attenuation of calcification by Ang II. Conclusion As hypothesized, Ang II prevented phosphate‐induced calcification in VSMCs, which appears mediated by the increase of magnesium influx and by the activation of the ERK1/2 and the inhibition of the canonical Wnt/beta‐catenin signalling pathways.